EVALUASI TERHADAP PELAKSANAAN ADMINISTRASI KESISWAAN PADA SEKOLAH MENENGAH PERTAMA NEGERI 1 KUSAN HILIR KABUPATEN TANAH BUMBU - Ade Hermawan (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: The implementation of Student Administration at Kusan Hilir 1 Junior High School includes student planning activities, admission of new students, recording of students in the master book, administration of student attendance, school discipline, student transfer, student organization activities, and administration of graduation and alumni. All student administration activities have been done well by the administration staff of the Kusan Hilir 1 Junior High School. Factors Influencing the Implementation of Student Administration at the 1 Kusan Hilir State Middle School are education of administrative staff and the availability of facilities and infrastructure owned by Kusan Hilir 1 Junior High School. Keyword: Evaluation of Implementation, Student Administration, SMP Negeri 1 Kusan Hilir Abstrak: Implementasi Administrasi Siswa di SMP Kusan Hilir 1 meliputi kegiatan perencanaan siswa, penerimaan siswa baru, pencatatan siswa dalam buku induk, administrasi kehadiran siswa, disiplin sekolah, pemindahan siswa, kegiatan organisasi siswa, dan administrasi kelulusan dan alumni. Semua kegiatan administrasi siswa telah dilakukan dengan baik oleh staf administrasi SMP 1 Kusan Hilir. Faktor-faktor yang Mempengaruhi Penerapan Administrasi Siswa di Sekolah Menengah Negeri 1 Kusan Hilir adalah pendidikan staf administrasi dan ketersediaan fasilitas dan infrastruktur yang dimiliki oleh SMP 1 Kusan Hilir. Kata Kunci: Evaluasi Pelaksanaan, Administrasi Kesiswaan, SMP Negeri 1 Kusan Hilir